Terahertz Reflectarray: Terahertz Reflectarray with Enhanced Bandwidth (Advanced Optical Materials 20/2019). Issue 20 (21st October 2019) - You, Xiaolong; Ako, Rajour T.; Lee, Wendy S. L.; Low, Mei Xian; Bhaskaran, Madhu; Sriram, Sharath; Fumeaux, Christophe; Withayachumnankul, Withawat
Abstract : A single‐layer stub‐loaded terahertz resonator is presented for constructing reflectarrays with enhanced bandwidth in article number 1900791 by Xiaolong You and co‐workers. A focusing reflectarray that transforms the incident collimated beam into a focused beam is realized using this resonator as a building element, exhibiting improved bandwidth as intended. The reflectarrays constructed by this resonator can be applied for various beamforming functions with applications in terahertz communications, sensing and imaging.